Secret rain in the clouds of Cape Verde - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
In a country where it hardly ever rains, it may be better to live high in the mountain mists, even if this means that farmers have to be skilled mountaineers as well. For farmers in Cape Verde because the slopes are so steep everything the farmers...